Taxonomic and Evolutionary Significance of Biogenic Amines and Polypeptides in Amphibian Skin. II. Toads of the Genera Bufo and Melanophryniscus - Cei, José Miguel Alfredo María (1968)
The value of the study of biogenic amines and active polypeptides of the amphibian skin in providing taxonomic evidence has been pointed in an earlier paper (Cei, Erspamer and Roseghini, 1967). The point was stressed that biochemical taxonomy, in its broadest sense, is possibly more discriminating than traditional taxonomy, based on somatic or osteological structures, size or coloration. In the first paper of this series sets of biochemical and pharmacological data concerning the skins of lep- todactylid frogs were reported and discussed. The present paper deals similarly with representatives of another very important family of Procoela, the Bufonidae.